1997
DOI: 10.1136/jnnp.63.5.597
|View full text |Cite
|
Sign up to set email alerts
|

Temporal lobe abnormalities in dementia and depression: a study using high resolution single photon emission tomography and magnetic resonance imaging

Abstract: Objectives-Perfusion SPECT and MRI were used to test the hypothesis that late onset depression is associated with brain abnormalities. Tcexametazime (HM-PAO). Temporal lobe templates were fitted with brains pitched by 20°-30°. A subgroup of 41 patients (22 depressed) were also scanned using a Siemens Magnetron 1.0 Tesla magnetic resonance imager, using a FLAIR imaging sequence for the assessment of white matter hyperintensities, and a Turbo FLASH sequence for the measurement of medial temporal lobe width. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 49 publications
(19 reference statements)
2
14
0
Order By: Relevance
“…Since depression is a risk factor for AD, only careful long-term follow-up of cases reported here who have atrophy will determine whether they are at increased risk of developing AD. Overall, although mild volume reductions in the hippocampus of 10-15% have been reported in chronic depression [4], our results are consistent with the findings of Ebmeier et al [14] who reported that mean MTL width on MRI was significantly greater in depressed subjects than in those with AD. Although structural brain changes and enduring cognitive impairments are known to occur in elderly depressed subjects [14,15].…”
Section: Discussionsupporting
confidence: 83%
“…Since depression is a risk factor for AD, only careful long-term follow-up of cases reported here who have atrophy will determine whether they are at increased risk of developing AD. Overall, although mild volume reductions in the hippocampus of 10-15% have been reported in chronic depression [4], our results are consistent with the findings of Ebmeier et al [14] who reported that mean MTL width on MRI was significantly greater in depressed subjects than in those with AD. Although structural brain changes and enduring cognitive impairments are known to occur in elderly depressed subjects [14,15].…”
Section: Discussionsupporting
confidence: 83%
“…Such temporal lobe dysfunction in LOD was reported by Ebmeier et al, 40,41 who investigated rCBF using SPECT. They found that patients with LOD exhibited decreased rCBF in the temporal areas of the cortex compared with those with EOD and emphasized the temporal lobe pathology of LOD.…”
Section: Discussionmentioning
confidence: 85%
“…Recent studies have also pointed out the presence of a decreased basal ganglia rCBF in AD patients [14][15][16]. Other investigations have stressed the involvement of the anterior as well as the posterior cingulate cortex in both AD and FLD [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…In general, such studies have preferably been focused on the tracer distribution in cortical brain tissues. The changes caused by AD and FLD on central structures [14][15][16] and the anterior [17,18] and posterior [19] cingulate cortex have seldom been studied. Most brain SPECT studies have been evaluated and analysed by visual rating of rCBF or outlining the regions of interest in a manual or semi-automatic mode, and building up ratios between reference and target regions.…”
Section: Introductionmentioning
confidence: 99%